G136 An unusual case of alopecia in a toddler. (May 2019) - O'Sullivan, GM; Shivamurthy, VM; Semkova, K; Mellerio, JE
Abstract : A two year old, Caucasian boy presented with an annular plaque over his forehead and anterior scalp with associated alopecia. This was occasionally itchy and was slowly increasing in size. There was no history of other skin problems. He had a single kidney due to previous hydronephrosis from posterior urethral valves. There was no relevant family history. There was no response to treatment with anti-fungal cream, shampoo and topical steroids. On examination there was a 20 cm annular atrophic violaceous mildly indurated plaque extending across the forehead and into the scalp. There was associated non-scarring alopecia. Mycology was negative on four separate occasions. Skin biopsies from the scalp showed histopathological findings of a dense perifollicular infiltrate in the deep dermis and superficial subcutaneous tissue comprising histiocytes, lymphoid cells and plasma cells. The lymphoid cells showed occasional atypia and were a mixture of T- and B-cells with a significant number expressing CD123 as well. Blood work was essentially normal including negative rheumatoid factor, ANA, anti-double stranded DNA, ENA and tissue specific antibodies. After clinico-pathological correlation the changes were felt to be in keeping with lupus profundus. He responded well to oral steroids with resolution of the erythema and regrowth of hair over his scalp although he is left with residual subcutaneous atrophy. He had paediatric rheumatology evaluation and there was no clinical evidence of underlying systemic autoimmune or inflammatory condition. He was commenced on hydroxychloroquine and is being monitored. Lupus profundus is an unusual variant of lupus erythematous. It is rare in children, with only 12 cases fully reported in the English literature 1 . Usually lupus profundus has a predilection for the proximal limbs, buttocks and shoulders. In children the most common site of involvement is the face 2 . It tends to run a chronic course. The condition can occur in isolation or as part of DLE or SLE so it is advisable to get a paediatric rheumatology opinion. Treatment options which can be considered include antimalarials, systemic steroids, dapsone or methotrexate. Patients tend to respond to treatment but the condition may relapse when treatment is discontinued 3 . References: Weingartner JS, Zedek DC, Burkhart CN, Morrell DS. Lupus erythematosus panniculitis in children: Report of three cases and review of previously reported cases. Pediatr Dermatol 2012 March-April;29(2):169–76. Fraga J, García-Díez A. Lupus erythematosus panniculitis. Dermatol Clin 2008 October;26(4):453–63. Park HS, Choi JW, Kim BK, Cho KH. Lupus erythematosus panniculitis: clinicopathological, immunophenotypic, and molecular studies. Am J Dermatopathol 2010 February;32(1):24–30.